Trading options Greeks how time, volatility, and other pricing factors drive profits - Passarelli, Dan, 1971- (Bloomberg financial series, 2012)
"A top options trader details a practical approach for pricing and trading options in any market conditionThe options market is always changing, and in order to keep up with it you need the greeks--delta, gamma, theta, vega, and rho--which are the best techniques for valuing options and executing trades regardless of market conditions. In the Second Edition of Trading Options Greeks, veteran options trader Dan Pasarelli puts these tools in perspective by offering fresh insights on option trading and valuation.An essential guide for both professional and aspiring traders, this book explains the greeks in a straightforward and accessible style. It skillfully shows how they can be used to facilitate trading strategies that seek to profit from volatility, time decay, or changes in interest rates. Along the way, it makes use of new charts and examples, and discusses how the proper application of the greeks can lead to more accurate pricing and trading as well as alert you to a range of other opportunities. Completely updated with new material Information on spreads, put-call parity and synthetic options, trading volatility, and advanced option trading is also included Explores how to exploit the dynamics of option pricing to improve your trading Having a comprehensive understanding of the greeks is essential to long-term options trading success. Trading Options Greeks, Second Edition shows you how to use the greeks to find better trades, effectively manage them, and ultimately, become more profitable"--